AMPK Activation Mediated by Hinokitiol Inhibits Adipogenic Differentiation of Mesenchymal Stem Cells through Autophagy Flux - Ju-Hee Lee; Jae-Kyo Jeong; Sang-Youel Park (International Journal of Endocrinology)
Background and Purpose. Hinokitiol, a natural monopenoid present in the essential oil of Calocedrus formosana heartwood, exerts potent anticancer, anti-inflammatory, antibacterial, and neuroprotective effects on various cells. However, the antiobesity effect of hinokitiol on adipocytes is unclear. Experimental Approach. In this study, we observed that hinokitiol affected the differentiation to adipocytes in mesenchymal stem cells (MSCs). Hinokitiol was treated with 3-isobutyl-1-methylxanthine, insulin, and dexamethasone to induce differentiation and maturing adipocytes in cultured MSCs. Key Results. Hinokitiol treatment of MSCs decreased their differentiation to mature adipocytes and increased AMPK phosphorylation in a concentration-dependent manner. Moreover, we confirmed that the antiadipogenic effect of hinokitiol was associated with autophagy. The levels of LC3-II decreased and those of p62 increased in hinokitiol-treated MSCs. The treatment of hinokitiol-treated MSCs with the autophagy activator, rapamycin, restored the hinokitiol-induced decrease in the adipocyte differentiation of MSCs. The inhibition of AMPK phosphorylation also suppressed hinokitiol-mediated inhibition of autophagy and antiadipogenic effects. Conclusions and Implications. Taken together, these results indicated that AMPK activation and autophagy flux inhibition mediated by hinokitiol inhibited lipid accumulation and differentiation of MSCs to adipocytes and also suggest that differentiation of mesenchymal stem cells may be regulated by using the modulator of autophagy flux and AMPK signals including hinokitiol.